Quick Overview of Extension Programs to Educate Homeowners about Environmentally-Friendly Landscape Practices in Florida, South Carolina, and Tennessee - Tatiana Borisova; Katie Giacalone; Ruth Anne Hanahan; Esen Momol (EDIS)
Nationwide, landscape irrigation accounts for more than 7 billion gallons of water per day. But up to 50 percent of this water is wasted due to overwatering, poor irrigation system design, evaporation, or other factors. Additionally, excessive or poorly timed fertilizer application can cause pollution runoff and deterioration of surface and ground water. This 8-page fact sheet presents a quick overview of the Yards and Neighborhoods program that educates homeowners about nine core principles for landscape management. Written by Tatiana Borisova, Katie Giacalone, Ruth Anne Hanahan, and Esen Momol, and published by the UF Department of Food and Resource Economics, August 2011. (UF/IFAS Photo Thomas Wright)